Clinical‐pathological features in placentas of pregnancies with SARS‐CoV‐2 infection and adverse outcome: case series with and without congenital transmission. (22nd April 2022) - Zaigham, Mehreen; Gisselsson, David; Sand, Anna; Wikström, Anna‐Karin; von Wowern, Emma; Schwartz, David A.; Iorizzo, Linda; Nelander, Maria; Blomberg, Marie; Papadogiannakis, Nikos; Holmström, Sandra; Leijonhfvud, Åsa; et al.
Abstract: Objective: To correlate clinical outcomes to pathology in SARS‐CoV‐2 infected placentas in stillborn and live‐born infants presenting with fetal distress. Design: Retrospective, observational. Setting: Nationwide. Population: Five stillborn and nine live‐born infants from 13 pregnant women infected with SARS‐CoV‐2 seeking care at seven different maternity units in Sweden. Methods: Clinical outcomes and placental pathology were studied in 14 cases (one twin pregnancy) of maternal SARS‐CoV‐2 infection with impaired fetal outcome. Outcomes were correlated to placental pathology in order to investigate the impact of virus‐related pathology on the villous capillary endothelium, trophoblast and other cells. Main outcome measures: Maternal and fetal clinical outcomes and placental pathology in stillborn and live‐born infants. Results: Reduced fetal movements were reported (77%) and time from onset of maternal COVID‐19 symptoms to signs of fetal distress among live‐born infants was 6 (3–12) days and to diagnosis of stillbirth 11 (2–25) days. Two of the live‐born infants died during the postnatal period. Signs of fetal distress led to emergency caesarean section in all live‐born infants with umbilical cord blood gases and low Apgar scores confirming intrauterine hypoxia. Five stillborn and one live‐born neonate had confirmed congenital transmission. Massive perivillous fibrinoid deposition, intervillositis and trophoblast necrosis were associated with SARS‐CoV‐2 placental infection and congenital transmission. Conclusions: SARS‐CoV‐2 can cause rapid placental dysfunction with subsequent acute fetal hypoxia leading to intrauterine fetal compromise. Associated placental pathology included massive perivillous fibrinoid deposition, intervillositis and trophoblast degeneration. Tweetable abstract: SARS‐CoV‐2 can cause rapid placental dysfunction and intrauterine fetal compromise. Linked article: This article is commented on by Yves Ville, pp. 1375 in this issue. To view this minicommentary visit https://doi.org/10.1111/1471-0528.17162 . This article includes Author Insights, a video abstract available at: https://vimeo.com/bjogabstracts/authorinsights17132